Analisis Tindak Tutur Lokusi pada Video Bertema Mental Health dalam Saluran Youtube Satu Persen Indonesia Life School - Choirunnisa Aprilia; Fathiya Salama; Haula Inayatul Ilahiyah; Natasya Intan Maharani; Surya Maulana; Yesica Mai Tuwanti Br Purba; Asep Purwo Yudi Utomo; Tomi Wahyu Septarianto (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
Every human being must have interactions between individuals, so a means of communication is needed by using language and various tools used to convey information. The purpose of this study is to analyze speech acts that contain locution in the YouTube channel One Percent - Indonesia Life School which discusses mental health issues or Mental Health. This method is used to describe a group of speech acts among the content writers of Satu Persen Indonesia Life School. This analysis is carried out by looking at the video properly, correctly, and carefully so as to produce accurate data in accordance with the creator's speech in the learning video. Locution speech act is a speech act that functions as an utterance that states something without the intention of doing something or influencing its partners. The results revealed three categories of locutionary speech acts, namely news locution, command locution, and question locution, with a total of 20 locutions identified. News locution is the most dominant categorinterak 13 speech acts, while command locution and question locution are 13 each. This research makes a theoretical contribution to the development of linguistics, especially in the field of pragmatics. The method used is the pragmatic approach, this approach focuses on how language and literary texts are used in certain social and cultural situations, as well as how the meaning of the text is understood.